Two green synthesis methods to prepared nanoparticles of Ag-two sizes and shapes via using extract of M. dubia leaves - Jahil, Mustafa Mudhafar; Zainol, Ismail; Jaafar, C. N. Aiza; H. A., Alsailawi; Majhool, Alhussein Arkan (American Scientific Publishers, 2020)
The effect of the synthesis technique on the shape and size of Ag-NPs has been reported. Ag nanoparticles has been produced by using two techniques, green synthesis and microwave-assisted green synthesis methods (MSGS), respectively. The current research was included to use a stabilizer and reducing agents from natural sources to get the non-toxic and environmentally friendly product, via using Melia dubia (neem) (M. dubia) and fish scales collagen (FsCol). The nanoparticles of Ag was portrayed by using Scanning electron microscope (SEM), Ultraviolet-visible spectroscopy (UV-vis), Energy-dispersive X-ray spectroscopy (EDX), Fourier-transform infrared spectroscopy (FTIR), Dynamic Light Scattering (DLS) and X-ray Powder Diffraction (XRD). Two different absorbance peaks were noticed in UV-vis and located at 454 nm silver nanoparticles-1 (AgNPs-1) and 446 nm silver nanoparticles-2 (AgNPs-2). SEM was shown two different shapes rod (AgNPs-1) and spherical (AgNPs-2 shapes. EDX confirmed the presence of Ag as a single element at 3 KeV. FTIR was shown fictional groups that were surrounded by silver nanoparticles C2H2 C=O, N-H groups was an indication. XRD was shown thus that the AgNPs formed in this modern prepared are crystalline with two different sizes 120.20 and 84.30 nm, corresponding to AgNPs-1 and AgNPs-2. The Z-average in DLS for AgNPs-1 has been shown average size at 437.8 nm while AgNPs-2 was shown 121 nm in its size.